So, even though I know how to solve ODEs, I don't know how I should proceed about this question:

Let $a$, $b$, and $c$ positive constants. If $y = y(x)$ is solution to the differential equation $ay'' + by' + cy = 0$, then $\lim_{x\to\infty}$ $y(x)$:

(a) doesn't exist and tends to $+\infty$.
(b) exists and is $0$.
(c) doesn't exist and tends to $-\infty$.
(d) exists and is $\pi$.
(e) exists and is $e$.

I tried to take the limit of the possible solutions but even if $a$, $b$, and $c$ are positive-only numbers, there are many possibilities so I couldn't achieve anything.

Thanks for the reading!

  • 2
    $\begingroup$ It depends on the roots of the characteristic equation. If both roots (or the real parts of the roots are negative) then you have a sink. If not, you don't. $\endgroup$
    – Doug M
    Commented Jun 26, 2018 at 4:47

5 Answers 5


According to the Laplace final value theorem for a stable system under initial conditions,

$$ \lim_{t\to\infty}y(t) = \lim_{s\to 0}sY(s) $$

and here

$$ Y(s) = \frac{s \dot y(0)+y(0)}{a s^2+bs+c} $$

which is the Laplace transform for $y(t)$. Here the poles are

$$ s^* =\frac{-b\pm\sqrt{b^2-4ac}}{2a} $$

then as $\left(\frac{-b}{2a}\right) < 0$ the system response is stable and under those conditions we have

$$ \lim_{t\to\infty}y(t) = \lim_{s\to 0}sY(s) = 0 $$

  • 2
    $\begingroup$ I suppose that given the context, a reader would be able to guess that $Y(s)$ represents the Laplace transform, but it would be good to explicitly state so. $\endgroup$ Commented Jun 26, 2018 at 14:47
  • $\begingroup$ This is what I came for $\endgroup$
    – Paul Evans
    Commented Jun 26, 2018 at 23:12

There are indeed several possibilities, but I wouldn't necessarily call that "many". And the key is that all three coefficients $a$, $b$, and $c$ are positive real numbers.

The roots of the characteristic equation are $$\lambda_{1,2}=\frac{-b\pm\sqrt{b^2-4ac}}{2a}=-\frac{b}{2a}\pm\frac{\sqrt{b^2-4ac}}{2a}.$$ Jumping ahead, the $\displaystyle \color{red}{-\frac{b}{2a}}$ part, which is obviously a negative number here, is the key! Anyways, now we only have three significantly different cases based on the discriminant.

  • If $b^2-4ac>0$, then we have two distinct real roots, and it's easy to see that both $\lambda_{1,2}$ are negative.

  • If $b^2-4ac=0$, then we have a repeated real root $\displaystyle\lambda_{1,2}=-\frac{b}{2a}$, which is again a negative number.

  • If $b^2-4ac<0$, then we have two complex conjugate roots, whose real part is the same negative value $\displaystyle -\frac{b}{2a}$.

Setting up the corresponding solutions $y(x)$ in all three cases leads to functions that have the same limit as $x\to+\infty$. In the first case the solution is a linear combination of $e^{\lambda_1}$ and $e^{\lambda_2}$, where both $\lambda_{1,2}<0$; and in the second and third cases the key is that the solution has a factor of $e^{-b/(2a)}$ (times something that doesn't grow fast enough or doesn't even grow at all).



$a, b, c > 0, \tag 1$

we can set

$\alpha = \dfrac{b}{a}, \; \beta = \dfrac{c}{a}, \tag{2}$

and obtain an equivalent equation

$y'' + \alpha y' + \beta y = 0, \; \alpha, \beta > 0; \tag{3}$

then setting

$\mu_\pm = \dfrac{1}{2}(-\alpha \pm \sqrt{\alpha^2 - 4 \beta}), \tag 4$

we may distinguish two cases: first

$\alpha^2 \ne 4 \beta, \tag 5$


$\sqrt{\alpha^2 - 4\beta} \ne 0, \tag 6$

and the roots $\mu_\pm$ are thus distinct; in this case the general solution is of the form

$y(t) = c_+ e^{\mu_+ t} + c_- e^{\mu_- t}; \tag 7$

since from (4) each of $\mu_\pm$ has negative real part,

$\displaystyle \lim_{t \to \infty} y(t) = 0; \tag 8$

if, on the other hand,

$\alpha^2 = 4\beta, \tag 9$

then we may write

$\mu_+ = \mu_- = \mu = -\dfrac{\alpha}{2} < 0, \tag{10}$

and the solution now takes the form

$y(t) = e^{\mu t}(c_1 + c_2 t) \to 0 \; \text{as} \; t \to \infty, \tag{11}$

since the exponential term dominates $c_1 + c_2 t$ for $t$ sufficiently large.

In any event, whether $\mu_+ = \mu_-$ or not, we have $\lim_{t \to \infty} y(t) = 0$; thus (b) is the correct result.

Just to verify that $t e^{\mu t}$ solves (3): if

$y(t) = te^{\mu t}, \tag{12}$


$y'(t) = e^{\mu t} + \mu t e^{\mu t}; \tag{13}$

$y''(t) = \mu e^{\mu t} + \mu e^{\mu t} + \mu^2 t e^{\mu t} = \mu^2 t e^{\mu t} + 2 \mu e^{\mu t}; \tag{14}$

$y''(t) + \alpha y'(t) + \beta y(t) = \mu^2 t e^{\mu t} + 2 \mu e^{\mu t} + \alpha \mu t e^{\mu t} + \alpha e^{\mu t} + \beta t e^{\mu t}$ $= (\mu^2 + \alpha \mu + \beta) t e^{\mu t} + (\alpha + 2 \mu) e^{\mu t} = 0 \tag{15}$


$\mu^2 + \alpha \mu + \beta = (\mu + \dfrac{\alpha}{2})^2 = 0 = 2\alpha + \mu, \tag{16}$

which follows from (4) when (9) binds.

  • $\begingroup$ Robert, your answer is correct according to the answer list, but how can you be sure that $\alpha^2 > 4*\beta$? $\endgroup$ Commented Jun 26, 2018 at 11:49
  • 1
    $\begingroup$ @CésarSilva - You don't need to be: the real part of the complex root is still negative, and that's all that matters. $\endgroup$ Commented Jun 26, 2018 at 11:53
  • $\begingroup$ Even though the final answer is correct, your explanation is incomplete: if the roots are equal, the general solution has a different form. $\endgroup$
    – zipirovich
    Commented Jun 26, 2018 at 12:35
  • $\begingroup$ @zipirovich: Yes, you are correct; will edit. Thanks! $\endgroup$ Commented Jun 26, 2018 at 15:20
  • $\begingroup$ @zipirovich: OK, I patched up my solution! Cheers! $\endgroup$ Commented Jun 26, 2018 at 16:33

Note that your differential equation is linear. If $y$ is a solution to your problem, then $\lambda y$ is also a solution to your equation. No initial conditions are given in your problem.

Consequently, if $\lim_{x\rightarrow\infty} y(x)$ has value $A$ (where $A$ is possibly $\pm\infty$), then $\lim_{x\rightarrow\infty} \lambda y(x)$ has value $\lambda A$.

Given that one of the answers a to e is correct, so knowing that $A$ exists, the only way it can be uniquely defined if is $A=\lambda A$ for all $\lambda$, or in other words $A=0$, and answer b is correct.


Always check for the trivial solution. $y \equiv 0$ is a solution of the given equation. This makes answer (b) correct. (The other correct answers here arrive at the same conclusion by other means.)


You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .